(3ebGdI KGhaQSWGjS GdYe dMLL CQSWhWGdjS aj eGHYO GdWHjYIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s ((3jMi Hf LQjQ GdeJWHH s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3efgeG efaUd Yf GdGNQ Ef GdGTjGA GdeYbhdI EfeG gi ai GdJYGdje abW Ydi eG jbhd HYV GdfGS s
(3BNQgG (B:s
(3aGf gPG eHOC GdfXQ ai Gdcd hGjVkG ai Ci GdGTjGA hLhO GdehLhOGJ hcja MGdgG HYVgG YfO HYV s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdadSaI hGdefWbs